Data for the Domestic Rabbit’s Drinking Water Supply - Bodnár, Károly (Journal of Central European Green Innovation, 2022)
A short review article was prepared on the domestic rabbit's drinking water consumption and the external and internal factors that significantly influence it. The rabbit's need for drinking water is influenced, among other things, by age, sex, body weight, lactation phase and milk production, the dry matter, fiber and protein content of the feed, the mineral content of the water, the temperature of the water, the possibility of access to water and/or feed and the ambient temperature. The domestic rabbit's water consumption habits are partly derived from the ancestral behavior of the wild rabbit (Oryctolagus cuniculus), and partly influenced by the design of the drinkers. Continuous satisfaction of the rabbit's demand for drinking water in artificial housing conditions is a basic welfare requirement.
Keywords: rabbit; drinking water; animal welfare; water quality; drinkers